Predictors of Pediatric COVID-19 vaccination: a case-control study in Tabriz, Iran - Parvin Sarbakhsh; Nasrin Jafari; Saman Salemi; Reza Akbarnejad (BMC, 2023)
Abstract Introduction COVID-19 vaccination of children can help reduce the severity of the infection and the death rate caused by it and also helps achieve herd immunity. The level of acceptance and high vaccination coverage is the main elements in the success of immunization programs. Children's vaccination is dependent on their parent's decision. This study aims to identify predictors of the children's COVID-19 vaccination accomplishment by their parents. Method In this case-control study, 577 vaccinated children as cases and 366 un-vaccinated children as controls were randomly selected from the general population of Tabriz, Iran 2022, and their data were collected by telephone calls and interviews with the children's parents. Cases and controls were compared in terms of clinical and demographic factors of the child as well as the socioeconomic status (SES) of their parents by using a multivariable mixed-effect logistic regression model. Results According to the results of the multivariable logistic regression, the age of the child (OR = 1.26 95% CI (1.14, 1.40), p-value < 0.001), previous COVID-19 infection of the child (OR = 1.92, 95% CI (1.21, 3.04), p-value < 0.001), having no underlying disease in the child (OR = 1.76, 95% CI (1.02, 3.02), p-value = 0.04), the dwelling place of the household (the high-level dwelling in compared to a low level (OR = 3.34, 95% CI (1.6, 6.64), p-value = 0.001), the middle level of dwelling compared with low level (OR = 4.87, 95% CI (2.46, 9.51), p-value < 0.001)), and Father's job (Employee and technician Fathers compared to worker fathers (OR = 2.99, 95% CI (1.55, 5.77), p-value = 0.001)) were significant independent predictors of children COVID-19 vaccination. Conclusion Several demographic and socioeconomic factors were associated with children's vaccination. Older children, children without any underlying disease, children with a history of COVID-19 infection, and children of parents with higher levels of SES were more likely to receive the COVID-19 vaccine. This finding can be considered in children's vaccination policymaking.